2018
DOI: 10.1101/gad.310672.117
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans ADARs antagonize silencing of cellular dsRNAs by the antiviral RNAi pathway

Abstract: Cellular dsRNAs are edited by adenosine deaminases that act on RNA (ADARs). While editing can alter mRNA-coding potential, most editing occurs in noncoding sequences, the function of which is poorly understood. Using dsRNA immunoprecipitation (dsRIP) and RNA sequencing (RNA-seq), we identified 1523 regions of clustered A-to-I editing, termed editing-enriched regions (EERs), in four stages of development, often with highest expression in embryos. Analyses of small RNA-seq data revealed 22- to 23-nucleotide (nt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 62 publications
5
66
0
Order By: Relevance
“…In contrast, loss of the dsRNA degrading adenosine deaminases adr-1 and adr-2 results to high levels of endogenous dsRNAs that, in rrf-3 or eri-1 mutant backgrounds that eliminate the endogenous 26G RNA pathway and nuclear NRDE-3 (46), are converted into siRNAs that promote strong nuclear localization of NRDE-3 ( Fig. 7B) (59). Nuclear NRDE-3 can be similarly induced in response to exogenous dsRNA triggers (46).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, loss of the dsRNA degrading adenosine deaminases adr-1 and adr-2 results to high levels of endogenous dsRNAs that, in rrf-3 or eri-1 mutant backgrounds that eliminate the endogenous 26G RNA pathway and nuclear NRDE-3 (46), are converted into siRNAs that promote strong nuclear localization of NRDE-3 ( Fig. 7B) (59). Nuclear NRDE-3 can be similarly induced in response to exogenous dsRNA triggers (46).…”
Section: Discussionmentioning
confidence: 98%
“…The requirement for DCR-1 and RDE-4 in the suppression of sterility in prg-1; daf-2 double mutants suggests the involvement of a dsRNA intermediate, because RDE-4 interacts with its targets via a dsRNA interaction domain (57). Adenosine deaminases modify double stranded RNAs by converting adenine to inosine, which results in dsRNA destruction (58) and therefore precludes dsRNA processing into 1 o siRNAs by RDE-4/DCR-1 and subsequent creation of 2 o 22G RNAs (59). To investigate potential daf-2-dependent changes in dsRNA processing, we re-analysed previously published daf-2 RNA-seq data (60) and lists of previously defined daf-16dependent loci based on RNA microarrays (61).…”
Section: Analysis Of Dsrna and Sirna Levels In Response To Daf-2 Defimentioning
confidence: 99%
See 2 more Smart Citations
“…We previously suggested that downregulation of genes in ADAR mutants could be a consequence of the antagonistic relationship between RNA editing and RNAi (Goldstein et al, 2017). The possibility that ADAR genes and RNA editing itself are antagonistic to the RNAi process was raised previously as editing and RNAi both involve dsRNA substrates, transgene silencing was observed in ADAR double mutants, and changes in the amount of siRNAs generated in wild-type worms and those lacking both ADARs (Goldstein et al, 2017, Knight and Bass, 2002, Reich et al, 2018, Tonkin and Bass, 2003, Warf et al, 2012, Whipple et al, 2015, Wu et al, 2011. Hypersensitivity to exogenous RNAi is a phenotype related to the ERI/RRF-3 endogenous RNAi pathway (Simmer et al, 2002), which is also reflected by transgene silencing.…”
Section: Resultsmentioning
confidence: 99%